Reclaimed asphalt test specimen preparation assisted by image analysis - Lo Presti, D.; Hassan, N. A.; Khan, R.; Airey, G. (American Society of Civil Engineers, 2015)
This paper presents a laboratory investigation aimed at establishing a protocol for the production of homogeneous asphalt mixtures test specimens, incorporating reclaimed asphalt by using a gyratory compactor with coring and trimming works. Stone mastic asphalt specimens were compacted at the previously identified target densities with the final aim of obtaining specimens with a fixed and homogeneous air void distribution. A microstructural study was conducted to characterize the homogeneity in the air void distribution using X-ray computed tomography (CT) combined with image analysis techniques. The study concluded that the gyratory compactor is suitable for producing homogeneous test specimens for the specified mixtures and a set of detailed procedures has been proposed for the production of the compacted specimens and to perform the microstructural study.